Lead (Pb) and Cadmium (Cd) contents in mangrove crab Scylla serrata collected from several traditional markets in Medan City, Indonesia - Eri Yusni; Reni Z. Sinaga (Aceh Journal of Animal Science, 2018)
Magrove crab Scyllaserratalives in coastal area of city is  susceptible to contaminate by heavy metals. Therefore, the objective of the present study was to examine the heavymetalcontentofLead (Pb)andCadmium(Cd)inmangrovecrabS.serrataobtained from several traditional markets in the Medancity, Indonesia. The measurementofheavymetalcontentwascarriedoutusingtheAtomicAbsorption SpectrophotometerwiththeFurnaceGraphmethod.The samples were collected  from six marketsin Medan city i.e. Pancing, Sei Kambing, Petisah, Belawan, Jamin Ginting and Padang Bulan markets. Thereresultsshowed that the highestvalueofPbinwas in samplefrom Pancing (0.025mg kg-1)and Sei Sikambing (0.025mg kg-1) Markets  and lower was found in sample from Belawan market (0.013mg kg-1).  In addition, the  highestCadmium(Cd)contentisinPancing Market  (0.023 mg kg-1) and lower Cd was from  Belawan Market (0.101mg kg-1).  It was concluded that heavymetalsPbandCdineachsampleofmangrove crabswereclassifiedaslow level andstill met thequality standard threshold. Therefore,themangrovecrabsampleisstillsafeforconsumptionand canbeanexportcommodity. Keywords:  Mangrove crabs, heavy metals, pollution, AAS